Analisis Peranan Amil Zakat Hidayatullah Kota Medan dalam Meningkatkan Usaha Kecil Menengah Para Mustahik - Kurniawan Kurniawan; Yenni Samri; Juliana Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The purpose of this study was to determine the Analysis of the Role of Amil Zakat Hidayatullah City of Medan in Improving Small and Medium Enterprises for Mustahik This study uses a qualitative research method. The research method used is in-depth interviews on research subjects, observation and documentation. As for the research location, namely the Amil Zakat Hidayatullah Institute, Medan City, the data collection used in this study was Interview, Observation, Documentation The data analysis used in this study is descriptive analysis, where the aim of this analysis is to describe systematically, factually and accurately the facts and the relationship between the phenomena being investigated. The results of the role of amil zakat Baitul Maal Hidaytullah in utilizing zakat through the Indonesian cart and mosque program by increasing SMEs in the city of Medan have yielded quite good results. Given that programs or activities to improve SMEs to the community will provide more ways or opportunities and knowledge to them, not provide fish or money as working capital. Keyword: Amil Zakat, Mustahik, UKM